(untitled) (Eurasian Journal of Philology Science and Education, 2016)
This work is dedicated to the theory of algorithmic syntax of the simple Russian sentence. The theory of algorithmic syntax presents by itself the generative type of grammar as a result of the special structuring of the syntax of the simple question with the further process of learning the grammar. It was for this purpose that the unified virtual integral stemma of the Russian sentence and the algorithms for displaying grammatical material was developed, based on the theory of N. Chomski. Using L. Tenyer’s theory, different structural elements that form the simple sentence are being researched. All of the models constructed in the research, can be defined as the unification of the components, and can show the hierarchic relations among the components of those same models. In this research a visual representative system of teaching a second language is proposed.